The effects of midazolam on intraocular pressure in children during examination under sedation. Issue 8 (30th August 2010) - Oberacher-Velten, Isabel; Prasser, Christopher; Rochon, Justine; Ittner, Karl-Peter; Helbig, Horst; Lorenz, Birgit
Abstract : Background: To obtain reliable and accurate measurements of the intraocular pressure (IOP) in children often requires sedation or anaesthesia. Therefore, we investigated the effects of oral midazolam on IOP in children. Methods: In a prospective study, IOP was measured in 72 eyes of 36 cooperative children without glaucoma requiring general anaesthesia (mean age 3.5±1.3 years, body weight ≤20 kg) by using a Perkins hand-held tonometer. Measurements of IOP were performed before, and 15 and 30 min after sedation with orally administered midazolam (1 mg/kg) given as preoperative medication, and 5 and 15 min after induction of general anaesthesia. The individual IOP courses were analysed. Results: In all of the cooperative children, IOP measurement was possible after sedation with midazolam. Mean IOP was 11.2±0.3 mmHg before sedation, 10.9±0.2 mmHg at 15 min, and 10.7±0.3 mmHg 30 min after administration of midazolam. This small decrease was not statistically significant, whilst the IOP decline at 5 and 15 min after induction of general anaesthesia was statistically significant (p<0.0001). Conclusion: Sedation with midazolam can be assumed to be an applicable, well-tolerated, safe method for IOP measurements in children.